A Case Study of the Daytime Intense Radar Backscatter and Strong Ionospheric Scintillation Related to the Low‐Latitude E‐Region Irregularities. Issue 7 (17th July 2020) - Chen, Gang; Wang, Zhihua; Jin, Han; Yan, Chunxiao; Zhang, Shaodong; Feng, Jian; Gong, Wanlin; He, Zhiqiu
Abstract: The special daytime echoes, which present the V‐shaped echo pattern between 90–180 km ranges in the range‐time‐intensity (RTI) plot, were occasionally recorded by the Hainan coherent scatter phased array radar (HCOPAR) located at the low latitude of China. Four cases with distinct echo traces are presented to display the common characteristics of the V‐shaped echoes. They usually occur between 10:00–15:00 LT in the daytime with the enhanced top frequency and blanketing frequency of Es layer ( f t Es and f b Es). Their left/right wings present negative/positive Doppler velocity. A case on 16 August 2015 was investigated by the joint observation of the HCOPAR, the Hainan Digisonde, and a scintillation receiver. The echo spectra show that the V‐shaped echoes were backscattered from the type 2 irregularities. The formation of the V‐shaped echo pattern was due to the leakage of the antenna sidelobe for the very intense scatter from Es layer. The irregularities were found traveling westward with the velocity of 41.12 ± 2.08 m/s. While the occurrence of the intense irregularities, there were periodic peaks appearing on the f t Es and f b Es curves, and the maximum f t Es‐ f b Es reached 10.31 MHz. At the same time, the strong ionospheric scintillation event was recorded by the scintillation receiver. The wind shear is considered to produce the sharp density gradient in the Es plasma and then induce the gradient drift instability. The large‐scale gravity waves have the possibility to induce the E‐region wind shear. Key Points: Some scattered VHF echoes from daytime Es are so intense that they leak through antenna sidelobes to form V‐shaped echo pattern in RTI plot V‐shaped echoes on 16 August 2015 were accompanied with the strong scintillation event and the enhanced and periodic ftEs and fbEs peaks Wind shear is considered to produce the sharp density gradient in the intense Es layer and then induce the gradient drift instability